Adherence to colonoscopy at 1 year following resection of localized colon cancer: a retrospective cohort study. (23rd March 2018) - Neugut, Alfred I.; Zhong, Xiaobo; Lebwohl, Benjamin; Hillyer, Grace C.; Accordino, Melissa K.; Wright, Jason D.; Kiran, Ravi P.; Hershman, Dawn L.
Background: For patients with stages I-III colon cancer who have undergone surgical resection, guidelines recommend surveillance colonoscopy at 1 year. However, limited data exist on adherence and associated factors. We aimed to determine the rate of adherence to surveillance colonoscopy at 1 year among nonmetastatic colon cancer patients who underwent resection and factors associated with adherence. Methods: In this population-based retrospective cohort study, the Surveillance, Epidemiology, and End Results (SEER)–Medicare database was used. We identified patients with stages I-III colon cancer who underwent surgical resection and survived >3 years without recurrence (no chemotherapy after 8 months) from 2002–2011. Our primary outcome was a colonoscopy claim 10–15 months after resection. We used multivariable regression analysis to assess associations between sociodemographic and clinical factors and receipt of timely colonoscopy. Results: Among 28, 732 patients who survived >3 years without recurrence, 7967 (28%) did not undergo colonoscopy; 12, 033 (42%) had it at one year, with 3159 (11%) before 10 months and 5573 (19%) after 15 months. Decreased adherence was associated with older age; being male versus female; being black or Hispanic versus white; higher tumor stage; left-sided tumors versus right sided; and increased comorbidities. Chemotherapy receipt was associated with increased adherence (odds ratio 2.06; 95% confidence interval 1.88–2.24). Conclusions: In a large population-based sample of individuals aged ⩾ 65 years, only 42% of colon cancer survivors underwent 1-year surveillance colonoscopy. Demographic and clinical factors were associated with adherence.